Methods for agricultural input market reform research: a tool kit of techniques - Goletti, Francesco; Govindan, Kumaresan (International Food Policy Research Institute, 1995)
The purpose of this paper is to provide a research approach and a set of different quantitative techniques for analysis of questions related to agricultural input market reforms. The broad objective of the Multi Country Project 1 (MP 1) undertaken at the International Food Policy Research Institute is to understand the conditions for a successful reform of agricultural input markets, including the markets for fertilizers, pesticides, seeds, agricultural equipments and livestock services. This understanding requires an analysis of policy issues related to the overall economic environment, market structure, conduct and performance, transportation cost, traders' participation, demand for modern inputs and the impact and sequencing of reforms. This paper raises specific research questions addressing these policy issues and suggest possible research methods to answer those questions. Thus, the paper can be considered as a toolkit for the policy analysts interested in market reforms.